Investigation on the Thermal Stability of Refined Palm Oil Produced from Membrane-Based Refining Technique - Lau, W. j.; Ismail, A.F.; Razis, M.; Ng, B.C.; Goh, P.S.; Latip, R.A.; Othman, N.H. (Journal of Membrane and Separation Technology, 2013)
The main objective of this work is to study the heat stability of refined palm oil produced from membrane-based refining process. Two novel routes of refining process have been proposed in which the first one was to integrate conventional refining process with ultrafiltration (UF) membrane technology while the second route was based on the integration between conventional refining process and UF membrane-solvent extraction process. The results revealed that the two novel refining routes showed improvement on free fatty acid (FFA) stability compared with the conventional technique throughout 5-day studied period. With respect to peroxide value (PV), it is found that only the first proposed route showed very similar increasing trend with the conventional refining process. In addition to this, it is also found that the two refining routes which were operated at 260oC showed slightly better colour stability in comparison to conventionally-produced oil.